2020
DOI: 10.3389/fphar.2020.00200
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol Inhibits NLRP3 Signal Through YAP1 Activation to Alleviate Cholestatic Liver Injury and Fibrosis

Abstract: Cholestasis is common in multiple clinical circumstances. The NOD-like receptor protein 3 (NLRP3) inflammasome pathway has been demonstrated to play an important role in liver injury and fibrosis induced by cholestasis. We previously proved that MCC950, a selective NLRP3 inhibitor, alleviates liver fibrosis and injury in experimental liver cholestasis induced by bile-duct ligation (BDL) in mice. Herein, we investigate the role of calcipotriol, a potent vitamin D receptor agonist, in experimental liver cholesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 52 publications
(71 reference statements)
1
26
0
Order By: Relevance
“…However, as FXR expression is down-regulated in endotoxic mice, FXR synthetic ligands display a poor effect on cholestasis ( 136 ), thus advocating for the identification of an alternative therapeutic strategy such as promoting the increase of FXR expression. Finally, the VDR agonist calcipotriol is also able to alleviate cholestatic liver injury and fibrosis by inhibiting the NLRP3 inflammasome pathway involved in inflammation, and hepatic stellate cells activation likely responsible of fibrosis ( 166 ) ( Table 1 ).…”
Section: Regulatory Function Of Nr In Nlrp3-driven Diseases and Theirmentioning
confidence: 99%
“…However, as FXR expression is down-regulated in endotoxic mice, FXR synthetic ligands display a poor effect on cholestasis ( 136 ), thus advocating for the identification of an alternative therapeutic strategy such as promoting the increase of FXR expression. Finally, the VDR agonist calcipotriol is also able to alleviate cholestatic liver injury and fibrosis by inhibiting the NLRP3 inflammasome pathway involved in inflammation, and hepatic stellate cells activation likely responsible of fibrosis ( 166 ) ( Table 1 ).…”
Section: Regulatory Function Of Nr In Nlrp3-driven Diseases and Theirmentioning
confidence: 99%
“…According previous papers in other diseases, BRCC3-mediated deubiquitination of NLRP3 could be inhibited by VDR, and then NLRP3 activation is inhibited [18]. It has been proved that yes-associated protein 1 (YAP1) inhibit NLRP3 activation [36,37], and VDR agonist could negatively regulate NLRP3 in ammation activation through activating YAP1 [20]. NLRP3 in ammasome has a crosstalk with Aryl hydrocarbon receptor (AhR) and NF-κB [38], vitamin D3 can increase the activation of AhR signaling, AhR blocks NF-κB binding sites in the NLRP3 promoter region, which result to suppress NLRP3 in ammasome activation [39].…”
Section: Discussionmentioning
confidence: 93%
“…Untill now, the therapeutic effect of VDR agonist on LN has not been investigated, and the potential mechanisms are also unclear. Recently, it is reported that VDR inhibits NLRP3 activation which participated in LN development as described above in other diseases [18][19][20], at present the following issues need to clarify: 1) whether VDR agonist alleviates LN though inhibiting NLRP3 signal; 2) the molecular mechanism through which VDR inhibits NLRP3 signal.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NOX4 and NLRP3 are regulated by YAP/transcriptional coactivator with PDZ-binding motif (TAZ). 41,42 Therefore, the identified SREBP2 transactivation of YAP adds a new mechanism underlying EC inflammation and dysfunction. In line with this notion, atheroprone flow induces YAP, resulting in EC inflammation, proliferation, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Besides affecting the molecules detected in this study (eg, BIRC5, MCM6, AREG, CTGF, VCAM1, ICAM1, CYR61, CCNA1, and E2F1), the YAP pathway may also contribute to other SREBP2‐induced genes in ECs. For example, NOX4 and NLRP3 are regulated by YAP/transcriptional coactivator with PDZ‐binding motif (TAZ) 41,42 . Therefore, the identified SREBP2 transactivation of YAP adds a new mechanism underlying EC inflammation and dysfunction.…”
Section: Discussionmentioning
confidence: 99%